A Cyber-Pragmatics Analysis: ANIMAL EMOJIS AS K-POP IDOL REPRESENTATION - Hasan, Hani Firlyali; Sasmita, Rheina; Lubis, Ezra Rumatha; Simangunsong, Anisyah; Azura, Shakira Dwi; Putri, Dian Marisha (Universitas Harapan Medan, 2023)
In recent years, K-pop has expanded around all over the world, and its fans have created special ways that refer to their idols, such making use of animal emojis. This study examines how animal emojis are used in K-pop to convey alternate meanings, particularly when used in place of idol names. The study utilized a qualitative approach with the theory of reference as the theoretical framework. Data was collected from social media platforms, Twitter. The findings suggest that the use of animal emojis in K-pop culture serves as a form of the unique characteristics of the K-pop community and also a solution to convey meaning effectively within Twitter’s limitation characters. The discipline of cyber-pragmatics, or the study of language use in digital communication, is pertinent to this investigation. As a type of digital communication, the use of animal emojis in K-pop culture demonstrates how fans have adapted to the digital age and created their own language and communication style.